Lifestyle Sports in East Asia. (October 2019) - Evers, Clifton; Doering, Adam
"Lifestyle sports" are not the preserve of occidental cultures, even though late capitalist Western nations dominate them commercially and ideologically. Examples of these sports are snowboarding, BASE jumping, freestyle BMX, mountain biking, bouldering, skateboarding, kiteboarding, rock climbing, parkour/free running, windsurfing, and surfing. Non-occidental cultures—such as those in Asia, Latin America, and Africa—also influence lifestyle sport institutions, commodities, values, and practices. Arguably, this influence is expanding and is accelerating as the populations of non-occidental cultures champion their interests and perspectives. This article makes a modest proposal for the starting of a targeted discourse among those interested in the cultural politics of lifestyle sports in the region of East Asia, an area with its own unique international and intra-regional interactions and concomitant needs, desires, and perspectives. In specific regard to this region, we argue it is worth asking: What are the stories being narrated and what forms do they take? How are complex social, political, cultural, and economic relations of this region being negotiated through lifestyle sports?